Coupling and Shielding Properties of the Baffle in ICP System. (28th July 2011) - Brcka Brcka, Jozef Jozef; Robison Robison, R. Lee R. Lee
Abstract : This contribution is dealing with experimental and computational evaluation of the deposition baffle that is transparent to radio frequency (RF) magnetic fields generated by an external antenna in an inductively coupled plasma (ICP) source but opaque to the deposition of the metal onto a dielectric wall in ionized physical vapor deposition (IPVD) system. Various engineering aspects related to the deposition baffle are discussed. Among the many requirements focus is on specific structure of the slots and analysis to minimize deposition on the baffle (we used a string model for simulating the profile evolution) and deposition through the DB on dielectric components of the ICP source. Transparency of the baffle to RF magnetic fields is computed using a three-dimensional (3D) electromagnetic field solver. A simple two-dimensional sheath model is used to understand plasma interactions with the DB slot structure. Performance and possible failure of device are briefly discussed.